NGOs interventions for rural communities resilience to climate change and variability case study: Mulanje district, southern Malawi - Phiri, Chimwemwe (University of the Free State, 2020)
Climate change and variability is a huge developmental challenge for Malawi as it touches on key developmental issues facing human development. Given the country’s rurality and vulnerability to climate change, communities continue to face unprecedented impacts of climate change, which in the end impacts greatly on the economic, social, political and environmental components of society. Growing recognition of the role of Non-Governmental Organizations (NGOs) in climate resilience work offers hope in the climate change response discourse. Aside from many other varied roles in climate services, NGOs have been a key player in supporting resilience building for rural communities. Despite the emergency and presence of many NGOs, the impact and effectiveness require further exploration basically due to the fact that communities continue to remain vulnerable to climate shocks despite huge financial investment in the resilience-building processes. This study attempts to underscore the role and effectiveness of NGOs' interventions in regards to climate change, with a focus on Mulanje district in Malawi as a case study. The study’s central question is what is the role of NGOs and how are the interventions implemented by NGOs contributing to communities’ climate resilience? Data collection tools involved developed questionnaire guides that were administered through Focus Group Discussions (FGD) and Key Informant Interviews (KII). A total of 88 respondents were engaged, and their views were transcribed into themes that generated results.. Using Mulanje district, in Malawi as a case study, the study discovered that indeed NGOs are a possible alternative to the government in servicing the needs of vulnerable communities in regards to climate change resilience building. This is mostly manifested in its intermediary role in providing climate services such as knowledge, skills and resilience building interventions. Conclusions are drawn from the study centered on acknowledging the role of NGOs in providing new opportunities and innovations in resilience building and further highlight the need for strengthening the capacity of NGOs to effectively deliver climate change resilience building interventions. Furthermore, the study concludes that despite the commendable role played by NGOs, there is need to address ever emerging challenges in regards to flexibility, funding gaps as well as meeting project targets.
Dissertation (MDS (Development Studies))--University of the Free State, 2020
Keywords: Malawi Economic development; Climatic changes -- Africa -- Malawi; Climatic changes; Climate change and poverty; Non-governmental organizations